Problematika dan Solusi Pengembangan Materi Pendidikan Agama Islam Di Tingkat SMA/MA - Dikriati Kamalasari; Amaiwaty Arief; Rehani Rehani (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Learning difficulties, if not designed properly, can cause various problems both for the students themselves and for educators. Islamic religious education, one of the subjects that is required and tested both at the school level and the tertiary level by the Ministry of Religious Affairs of Jendra for Islamic Religious Education. Thus, as an alternative, it is important to develop Islamic religious endemic-learning materials in accordance with the relevance of the development of Islamic religious education. However, there are still problems and difficulties in Islamic religious education, both in learning and in the application of developing Islamic religious education learning materials. This research aims to find out the problems and solutions for the development of Islamic religious education materials at the high school/MA level. This research uses literature research with references from books, articles and analysis of existing problems. The results of this study are to find out what are the problems of the development of Islamic religious education materials at the high school level and what kind of solutions are presented to overcome these probelmatics.